Electron-plasmon model in the electron liquid theory - Vavrukh, M.V.; Slobodyan, S.B. (Condensed Matter Physics, 2005)
Here we propose an accurate approach to the description of the electron
liquid model in the electron and plasmon terms. Our ideas in the present
paper are close to the conception of the collective variables which was developed
in the papers of Bohm and Pines. However we use another body
of mathematics in the transition to the expanded space of variable particles
and plasmons realized by the transition operator. It is evident that in
the Random Phase Approximation (RPA), the model which consists of two
interactive subsystems of electrons and plasmons is equivalent to the electron
liquid model with Coulomb interaction. Запропоновано строгий підхід до опису моделі електронної рідини в
термінах електронів і плазмонів. Концептуально наша робота близька до підходу колективних змінних, який розроблявся в роботах
Бома і Пайнса. Проте ми використовуємо інший математичний
апарат, в якому перехід до розширеного простору змінних частинок та плазмонів виконується за допомогою оператора переходу.
Доведено, що у наближенні хаотичних фаз модель, яка складається
із двох взаємодіючих між собою підсистем електронів і плазмонів,
цілком еквівалентна моделі електронної рідини з кулонівською
взаємодією.